BRIDGING THE GAP: A QUALITATIVE ANALYSIS OF GENDERED PERCEPTIONS ON GOOD AND EFFECTIVE ENGLISH TEACHER - Dewi, Kadek Ayu Komala; Artini, Luh Putu; Wahyuni, Luh Gede Eka (Universitas Suryakancana, 2024)
This study endeavors to delve into the nuanced perceptions of male and female students regarding the attributes of a good and effective English teacher, employing a descriptive qualitative research design. Conducted at SMA Negeri 1 Tabanan, the research engaged three class representatives encompassing a total of 108 students. Through an open-ended questionnaire featuring 10 statements each on the qualities of a good and effective English teacher, a rich dataset emerged from the insights of 85 participants (55 females and 30 males), meticulously collected via a streamlined Google Form. The intriguing findings unveiled a distinctive trend among female students, who showcased a penchant for the emotional facets of teaching, placing a premium on qualities such as empathy, understanding, and sensitivity when conceptualizing an exemplary teacher. In contrast, their male counterparts demonstrated a pragmatic stance, valuing a teacher's keen awareness of their competency level. A unanimous agreement from both genders emerged, highlighting the pivotal role of a flexible and adaptable teaching approach for an English teacher's effectiveness, ensuring adept navigation of unforeseen challenges and the cultivation of a thriving learning environment for all students